African Americans and adult literacy education: Towards a more inclusive model of participation - Ronald M. James (Adult Education Research Conference, 1994)
The use of SES to explain non-participation is critiqued. Arguments are presented which demand that more serious study be given to structural factors related to race that affect participation.